In-situ catalytic growth carbon nanotubes from metal organic frameworks for high performance lithium-sulfur batteries. (June 2018) - Zhao, Jinxing; Liu, Cui; Deng, Heming; Tang, Shun; Liu, Chang; Chen, Shengrui; Guo, Jinglong; Lan, Qian; Li, Yuxiao; Liu, Yan; Ye, Miao; Liu, Honghao; et al.
Abstract: The highly uniformed hybrid carbon material has been prepared by in-situ growth carbon nanotubes (CNTs) from metal organic frameworks, with the cobalt species as the catalyst for CNTs growth and dicyandiamide (DICY) as a sacrificial agent for the formation of graphitic carbon. The CNTs with extraordinary conductivity supply more electron transport to the cathode and make much more sense in enhancing the rate performance of the sulfur cathode. In the matrix, cobalt nanoparticles and heteroatom nitrogen can help in immobilizing sulfur species, leading to the improvement of polysulfide shutting. Moreover, the increased specific surface area and mesoporous channel enhance the sulfur loading and facilitate electrolyte diffusion. On integrating these fascinating benefits into one electrode material, as a result, the hybrid composite (CNT@CoNC/S) cathode presents a high initial capacity of 1316.1 mAh/g at the current rate of 0.1C. Even at high current rate of 5C, a decent capacity of 620.7 mAh/g can still be achieved. The capacity of hybrids materials can be maintained at 970 mAh/g after 500 cycles at 0.2C, and a capacity retention of 79.8%, revealing it great potential for energy storage application. Graphical abstract: Highlights: An in-situ catalytic method is used to growth carbon nanotubes from metal organic frameworks. The composite CNT@Co-N-C has high specific surface area to accommodate S and abundant CNTs to improve the conductivity. The composite cathode demonstrates high rate and cycling performance.